Optimalisasi Pengoperasian Pipa Minyak Mentah Jalur Minas-Duri dengan Lean Sigma - Denny Astrie Anggraini; Rita Kusrina (UIN Sultan Syarif Kasim Riau, 2015)
As a business unit of oil and gas companies operating in Riau, in distributing the products, the company uses the pipeline that carries crude oil from Gathering to Terminal. One of the segments of pipe used is from North Booster Pump (NBS) Minas to Pungut that uses 2 pieces of carbon steel pipe with a diameter of 30